Acclimation of leaf respiration temperature responses across thermally contrasting biomes. Issue 3 (14th October 2020) - Zhu, Lingling; Bloomfield, Keith J.; Asao, Shinichi; Tjoelker, Mark G.; Egerton, John J.G.; Hayes, Lucy; Weerasinghe, Lasantha K.; Creek, Danielle; Griffin, Kevin L.; Hurry, Vaughan; Liddell, Michael; Meir, Patrick; et al.
Summary: Short‐term temperature response curves of leaf dark respiration ( R–T ) provide insights into a critical process that influences plant net carbon exchange. This includes how respiratory traits acclimate to sustained changes in the environment. Our study analysed 860 high‐resolution R–T (10–70°C range) curves for: (a) 62 evergreen species measured in two contrasting seasons across several field sites/biomes; and (b) 21 species (subset of those sampled in the field) grown in glasshouses at 20°C : 15°C, 25°C : 20°C and 30°C : 25°C, day : night. In the field, across all sites/seasons, variations in R 25 (measured at 25°C) and the leaf T where R reached its maximum ( T max ) were explained by growth T (mean air‐ T of 30‐d before measurement), solar irradiance and vapour pressure deficit, with growth T having the strongest influence. R 25 decreased and T max increased with rising growth T across all sites and seasons with the single exception of winter at the cool‐temperate rainforest site where irradiance was low. The glasshouse study confirmed that R 25 and T max thermally acclimated. Collectively, the results suggest: (1) thermal acclimation of leaf R is common in most biomes; and (2) the high T threshold of respiration dynamically adjusts upward when plants are challenged with warmer and hotter climates.